Eskalasi Potensi Santri melalui Pelatihan Adzan dan Diba’ di Madrasah Diniyah Al Aziz Sawahan Lengkong Nganjuk - Muda’i, Syaiful (LP3M STAI Darussalam Krempyang Nganjuk, 2019)
The potential of students who are in the village Madrasah Diniyah if traced more in the not yet well-explored, then to increase and maximize the potential must be touched through well-organized trainings, so that the potential to be excavated can be explored to the fullest. This is a qualitative study using the ABCD (asset based community Development) approach conducted in the village of Sawahan Lengkong Nganjuk. Data collection is conducting deep interviews to informant, observations, documentation studies and recordings. The result showed that The existence of Madin Al Aziz which is in the environment of Pesantren is quite helpful for the program that is proclaimed can run optimally.